Caracterização da entomofauna em áreas iniciais de restauração ecológica com sistemas agroflorestais (SAFs) e plantio misto com espécies nativas - Providello, Alexandra (Universidade Federal de São Carlos, 2019)
Agroforestry systems (AFS) are consortia of crops with tree species and can be used as an alternative for the ecological restoration of degraded forest ecosystems. However, little is known about the entomofauna in newly implemented systems. The objective of this study was to characterize the edaphic entomofauna in the initial areas of two models of ecological restoration: AFS and conventional restoration, under different weed management. The study was conducted at CCA/UFSCar, Araras, SP, in four areas (2,160m2 each): AFS with herbicide application (SAFh), AFS with mechanized brush cutting (SAFm), conventional herbicide restoration (RCh), and restoration with mechanized mowing (RCm). In the AFS areas, seedlings of 10 pioneer or secondary native tree species (n = 120) were planted, along with coffee as an agricultural species in the planting lines; in conventional restoration, only seedlings of 20 native tree species (n = 240) were planted. Entomofauna was collected in July and December 2017 using pitfall traps (n = 10), arranged in a transect 4 m equidistant from each other, and left in the field for 120 hours. A total of 11,472 individuals were sampled, distributed in 11 orders and 48 families. The most representative groups were Collembola (55.19%), Hymenoptera: Formicidae (32.28%), Coleoptera: Carabidae (3.62%), and Diptera: Cecidomyiidae (1.66%). A significant difference was observed in abundance (number of individuals per arm-1) between the areas by the Kruskal Wallis test (H = 15.45, p = 0.0014), but not for richness (n) and diversity (H) (P <0.05): SAFh (29, 1.21), SAFm (30, 1.04), CRh (28, 1.37), CRh (36, 1.52). Restoration models and weed control methods influenced only the abundance of insects. As these are areas in the early stages of the restoration process, monitoring will continue to evaluate possible changes in entomofauna dynamics.
Characterization of the entomofauna in early stages of ecological restoration with agroforestry systems (AFS) and mixed planting with native species
Keywords: Fauna edáfica; Restauração florestal; Consórcio agroflorestal; Edaphic fauna; Forest restoration; Agroforestry consortium; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES